ANALYSIS OF REFUTATIONS AGAINST QADARIYYA AND JABARIYYA SECTS IN THE WORK "ISHARAT AL-MARAM" BY KAMALUDDIN BAYADHI - Muhibullaev Saidmukhammadkhan Davudkhanovich (Scholar Express Journal, 2024)
This article analyzes the refutations given to the categories of Qadariya and Jabariya in the work of Kamoliddin Bayazi called "Ishorotul-marom min iborotil Imam Abi Hanifa". The Qadaris put forward the idea that "Allah, the Most High, does not predestined anything, He does what His servants do only out of His own will." Jabariyyah cites the evidence that all the deeds that God has not given to the servant will be as written in the destiny of the servant. It is known that both of the above situations are against the creed of Ahl al-Sunn wal-Jamaa
Keywords: Qadariya; Jabariya; Kamoliddin Bayazi